PENGARUH JARAK TANAM TERHADAP PERTUMBUHAN PADI ADAN KRAYAN (Oryza sativa L.) - Harfresen Harfresen; Rustam Baraq Noor; Iin Arsensi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
The purpose of the research was to the effect of row spacing on the growth of upland rice (Oryza sativa L.) Adan Krayan; and to find row spacing for better growth of upland rice Adan Krayan.The research carried out from July to October 2020 in Liang Bua Village,  Krayan Barat su-district, Nunukan Regency.The research used Completely Randomized Block Design (CRBD) with four treatment of row spacing and five replications namely: no uniform as control (p0), 30 cm x 30 cm (p1), 40 cm x 40 cm (p2), and 50 cm x 50 cm (p3).   The result of the research revealed that : (1) row spacing treatment affected significantly to very significantly on the plant height, number of leaf and number of a tiller at 30, 60, and 90 days after planting, and (2) the best of the growth was produced in 40 cm x 40 cm.